KLASIFIKASI KEMANCETAN LALU LINTAS DI INDONESIA MENGGUNAKAN METODE NAIVE BAYES CLASSIFICATION - Al Firdaus; Maftukhatusolikhah Maftukhatusolikhah; Rinol Sumantri (Ridwan Institute, 2021)
This research focuses on where the DSN MUI and its implementation of BMT institutions specialized in Murabahah products. Data source from leaders and members of 3 BMT. Mandatory Fatwa DSN MUI in each Sharia Financial Industry in this case BMT for sharia administrators which sharia supervision as separate as inseparable with sharia compliance (sharia compliance). This can be seen from some of the words strengthened by DSN MUI which became a reference for the Islamic Finance industry in its activities in the field of Sharia finance. This research is a field research on qualitative descriptive. Data analysis techniques use reduction technique data. The results of the analysis showed that: Murabahah financing in 3 BMT in Ogan Komering Ilir Regency is above Islamic sharia in murabahah financing agreement which is also brewing aka wakalah. Factors that cause not since Sharia at the event murabahah financing agreement again goods where the money there is a difficult variation quite a lot of materials in the form of buildings, so the BMT only provide financing, without buying the materials, then back to the money.